The Oxford handbook of talent management - Collings, David G.; Mellahi, Kamel; Cascio, Wayne F. (2017)
The Oxford Handbook of Talent Management' offers academic researchers, advanced postgraduate students, and reflective practitioners a state-of-the-art overview of the key themes, topics, and debates in talent management. The Handbook is designed with a multi-disciplinary perspective in mind and draws upon perspectives from, 'inter alia', human resource management, psychology, and strategy to chart the topography of the area of talent management and to establish the base of knowledge in the field. Furthermore, each chapter concludes by identifying key gaps in our understanding of the area of focus. 00The Handbook is ambitious in its scope, with 28 chapters structured around five sections. These include the context of talent management, talent and performance, talent teams and networks, managing talent flows, and contemporary issues in talent management. Each chapter is written by a leading international scholar in the area and thus the volume represents the authoritative reference for anyone working in the area of talent management.
Keywords: Personnel management; Knowledge management; Personnel management; Knowledge management; Personnel management; Begabung; Förderung; Karriereplanung; Personalpolitik